Construction of a Prognostic Model in Lung Adenocarcinoma Based on Ferroptosis-Related Genes - Liang, Min; Chen, Mafeng; Zhong, Yinghua; Singh, Shivank; Singh, Shantanu (Frontiers in Genetics, 2021)
Abstract: Background： Lung adenocarcinoma is one of the most common malignant tumors of the respiratory system, with the first morbidity and mortality among all cancers. This study aims to establish a ferroptosis-related gene-based prognostic model to investigate the potential prognosis of lung adenocarcinoma. Methods: We obtained gene expression data with matching clinical data of lung adenocarcinoma from the TCGA and GEO database. The ferroptosis-related genes (FRGs) were downloaded from from three subgroups in the ferroptosis database. Using gene expression differential analysis, univariate Cox regression, and LASSO regressionanalysis, seven FRGs with prognostic significance were identified. The result of multivariate Cox analysis was utilized to calculate regression coefficients and establish a risk-score formula that divided patients with lung adenocarcinoma into high-risk and low-risk groups. The TCGA results were validated using GEO data sets. Then we observed that patients divided in the low-risk group lived longer than the overall survival (OS) of the other. Then we developed a novel nomogram including age, gender, clinical stage, TNM stage, and risk score. Results: The areas under the curves (AUCs) for 3-year, 5-year OS predicted by the model were 0.823 and 0.852 respectively. Calibration plots and decision curve analysis also confirmed the excellent predictive performance of the model. Subsequently, gene function enrichment analysis revealed that identified FRGs are important in DNA replication, cell cycle regulation, cell adhesion, chromosomal mutation, oxidative phosphorylation, P53 signaling pathway, and proteasome processes. Conclusions: Our results verified the prognostic significance of FRGs in patients with lung adenocarcinoma, which may regulate tumor progression in a variety of pathways.